A STUDY OF SALT-AFFECTED SOIL CLASSIFICATION IN THE BASRA REGION WEST OF SHATT AL-ARAB - Samir , Ahmad Al-Khazaali; Al-Saadi , Hana Majeed (Ayden Journal of Agriculture and Allied Studies, 2024)
This study was conducted in the southern part of the alluvial plain, located within the administrative borders of Basra Governorate, confined between the Shatt Al-Arab to the east and the tidal flats (Spawn) to the west, between longitudes (-48.00°, -48.30°) east, and latitudes (-30.05°, -30.30°) north. Aimed to study of the impact of storming into salty marine waters, and its impact on the salinization of the lands adjacent to Shatt Al-Arab. About 2091 km2 The total area of the study area was estimated, to study some morphological, physical and chemical properties of soils. Study of the hydrochemical characteristics of groundwater in the study area. The extent to which this water and soil are affected by salinity coming from marine waters, during the tidal phase, which originates from Shatt Al-Arab stream and the Khor AlZubair channel, based on field work. The study area was deducted using Geographic Information A number of processing operations were carried out on it, including filling in gaps, correcting and making arc map corrections, which were corrected and converted into a digital image, then separated them into five categories based on the salt evidence. Spectral evidence relevant to the research topic Erdas 8.4 salt was calculated. The soil units were separated based on the salt index types. As typical and representative sites for soil pedons, five locations on Earth were selected using a GPS Global Positioning System.